URGENSI ASESMEN DALAM PENYUSUNAN PROGRAM BIMBINGAN DAN KONSELING DI SEKOLAH MENENGAH ATAS: SEBUAH STUDI KUALITATIF - Tisna Susanti; Wahidah Fitriani (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2022)
The research objective was to determine the urgency of the assessment in the preparation of guidance and counseling programs in senior high schools. The research method used in this study is a descriptive qualitative method. The subjects in this study were 16 guidance and counseling teachers at State Senior High Schools in Kabupaten Lima Puluh Kota. The data collection techniques in this study were through observation, interviews, and documentation studies. The results of the study stated that the position of the assessment was not too important because of the limitations of guidance and counseling teachers in compiling, implementing, and interpreting existing assessments. This has caused some schools to develop service programs not yet based on the assessments that have been carried out. Therefore, it is very necessary to provide guidance in compiling, implementing, and interpreting assessments for guidance and counseling teachers as a whole in the form of programs on guidance and counseling teacher deliberations as well as the active role of guidance and counseling supervisors, as well as elements of leadership in schools.